Improving the performance of double-pass EDFA utilizing chirped bragg grating as feedback loop - Jamaludin M.Z.; Bakar A.A.A.; Naji A.W.; Rahman F.A.; Mahdi M.A.; Abdullah M.K. (2023)
A new dispersion-compensated double-pass erbium-doped fiber amplifier (EDFA) with high gain and improved noise-figure characteristics is demonstrated using chirped fiber Bragg grating. The performance is compared with that of the conventional double-pass EDFA. The signal gain is improved by as much as 18.6 dB at -40-dBm signal power with negligible noise penalty. The proposed amplifier architecture can improve the signal gain and at the same time compensate the signal dispersion. 2005 Wiley Periodicals, Inc.